2020
DOI: 10.1177/2382120520936617
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Regional Medical Campuses to Ensure Comparable Experiences: Recommendations From a Narrative Review

Abstract: Background: Given increasing class sizes and desires to keep costs down, many medical schools are developing regional clinical campuses. We found our regional campus system to be very successful in allowing class size expansion, inspiring a workforce for the state, and concurrently allowing our students to individualize their experience. We desire to articulate our experience, with a review of the relevant evidence, with the goal of assisting other medical schools in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…4,5 The requirement creates a tension between striving to strengthen training in diverse contexts and delivering a standardized curriculum by reducing emphasis on the unique learning opportunities those contexts provide. 6 This tension may be the reason that comparability is one of the standards most commonly cited for noncompliance during accreditation. 4 In the United States, Canada, and Australia, the relevant standard requires that a "medical school ensures that the medical curriculum includes comparable educational experiences and equivalent methods of assessment across all locations within a given required learning experience to ensure that all medical students achieve the same learning objectives."…”
Section: Distributed Medical Education (Dme)mentioning
confidence: 99%
See 2 more Smart Citations
“…4,5 The requirement creates a tension between striving to strengthen training in diverse contexts and delivering a standardized curriculum by reducing emphasis on the unique learning opportunities those contexts provide. 6 This tension may be the reason that comparability is one of the standards most commonly cited for noncompliance during accreditation. 4 In the United States, Canada, and Australia, the relevant standard requires that a "medical school ensures that the medical curriculum includes comparable educational experiences and equivalent methods of assessment across all locations within a given required learning experience to ensure that all medical students achieve the same learning objectives."…”
Section: Distributed Medical Education (Dme)mentioning
confidence: 99%
“…Many articles cite specific standards for medical schools with 1 or more geographically distributed campuses. 6,9,14,18,21,23,24,[28][29][30] In articles that did not specifically refer to accreditation, authors offered concerns about educational quality in decentralized training locations, about whether the heterogeneity of clinical experiences and practitioners from community hospitals can maintain the same teaching standards as expected in academic teaching hospitals, and ultimately, whether differences in learning experiences may impact learning outcomes. 15,16,20,26,27,31,33…”
Section: Rationale For Educational Comparabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies exploring physician recruitment to rural areas have found that a history of rural upbringing or exposure can positively influence future rural medical practice. [17][18][19][20][21][25][26][27] Early exposure to target communities was shown as a strong indicator for successful physician recruitment and retention. [17][18][19]25 This exposure can engender familiarity, an important factor in establishing confidence when navigating the medical and social demands of a community.…”
Section: Solutionsmentioning
confidence: 99%
“…Exposure to rural communities via regional medical campuses or rotations during medical school has also been highly associated with future likelihood to practice in rural Pediatric Dermatology UGWU-DIKE anD naMBUDIRI locales. [17][18][19]25,27 Incorporation of rural training experiences directly into medical school, residency, and fellowship curricula can further augment exposure to such opportunities for all trainees.…”
Section: Solutionsmentioning
confidence: 99%